Screening Green Innovation through Carbon Pricing - Lassi Ahlvik; Inge van den Bijgaart (Center for Economic Studies and ifo Institute (CESifo), 2022)
Green innovation is essential for climate change mitigation, but not all innovative projects deliver equal social value. We consider innovator heterogeneity in a model where the policy maker cannot observe innovation quality and directly subsidize the socially most valuable green innovations. We find that carbon pricing works as an innovation screening device; this creates a premium on the optimal carbon price, raising it above the Pigouvian level. We identify conditions for perfect screening and generalize results to screening policies under alternative intellectual property regimes and complementary policies.
Keywords: O30; H23; Q55; Q58; 330; carbon pricing; green innovation; optimal policy; R&D; screening